Ekohidrologi Konsep Pengelolaan Lingkungan Berkelanjutan - Soeprobowati, Tri Retnaningsih (Bioma : Berkala Ilmiah Biologi, 2010)
Ecohydrology is the study on the interaction hydrological process or aquatic with biological dynamicspatially and temporarily. Ecohydrology promises to be a tool of the sustainable use of aquatic resources byecological analysis integrated with freshwater aquatic conservation. Methodologically, ecohydrology is amanagement tool using organism to control hydrological process and using hydrology to control biota. Basically,ecohydrology is water resource development that oriented on the capacity and ability to maintain it. Spatially, itrequires an understanding about the role of organism. Temporarily, it requires reconstruction on thepaleohydrology as a base of the water resource development that put global changes into account. Based on thesuccessful implementation of ecohydrological concept on Saguling Reservoir, it able to be implemented for anotheraquatic ecosystem.